LAPORAN PENANGGUNGJAWABAN TERAPI AKTIVITAS KELOMPOK (TAK) PADA KLIEN DENGAN DIABETES MELLITUS DI WISMA PISANG PANTI SOSIAL TRESNA WERDHA BUDI MULYA 2 JAKARTA BARAT TAHUN 2023 - Alfika Safitri; Muhamad Dian Permana Angga Dirja; Suci Ririn Puspita; Kasifah; Nurul Siti Khodijah; Rika Apriliana; Hesty Oktalia; Yulia Sartika Sari; Annisa Rahmawati; Tasya Rezky Amelia; Riska Elda Sari; Tuti Selfiani; Dewi Puji Astuti (Yayasan Nusantara Hasana Berdikari, 2023)
Introduction Diabetes mellitus is still an important health problem in the world, including in Indonesia, because cases continue to occur and are increasing (Nuraisyah, 2018). This disease is a metabolic disease characterized by chronic hyperglycemia resulting from damage/deficiency of insulin secretion, impaired response to insulin hormone or both (IDF, 2021 in Sutomo & Hadi, 2023). Diabetes Mellitus is not only the cause of death worldwide but is the main cause of blindness, heart disease and kidney failure (Ministry of Health of the Republic of Indonesia, 2020). The International Diabetes Federation in 2022 reports that 537 million adults (20-79 years) live with diabetes worldwide. This number is expected to increase to 643 million (1 in 9 adults) in 2030 and 784 million (1 in 8 adults) in 2045. Diabetes mellitus causes 6.7 million deaths in 2021. It is estimated that 44% of adults living with diabetes (240 million people) undiagnosed. 541 million adults worldwide, or 1 in 10, have impaired glucose tolerance, placing them at high risk of developing type 2 diabetes (IDF, 2021). The Ministry of Health of the Republic of Indonesia reports that the number of people with diabetes mellitus in 2021 is 19.47 million people (Ministry of Health RI, 2022). In Indonesia, the percentage of the population suffering from diabetes mellitus is 1.5% percent of the total population of Indonesia, which is approximately 172.5 million people. Diabetes mellitus (DM) is a condition that is often associated with an increased risk of morbidity and mortality. Elderly (elderly) who suffer from DM often also experience other diseases, physical disabilities, psychosocial disorders and cognitive function, as well as increased medical services. In the end, the complications that occur will affect the quality of life of the elderly (Simatupang & Mita Kristina, 2023). Type 2 DM is found in 85-90% of the total DM sufferers and is often found in the elderly. The highest prevalence of DM was found in residents aged ≥60 years with the highest incidence also found in that age group. The results of the Canadian Study of Health and Aging (CHSA) showed that the prevalence of DM was 12.1%. According to a survey conducted by the World Health Organization (WHO), Indonesia ranks 4th with the largest number of DM sufferers in the world after India, China and the United States. (Simatupang & Mita Kristina, 2023).